The World of a Person with a Disability: A Few Remarks on Dorota Terakowska’s Poczwarka - Socha, Kamila (Representations of Disability in Cultural Spaces, 2026)
The aim of this article is to analyse the novel Poczwarka by Dorota Terakowska in the context of the literary representation of the life of a child with Down syndrome and the challenges faced by its parents. The novel shows a deep reflection on the value of life, empathy and unconditional love, providing a literary starting point for a broader discussion on the social acceptance and integration of people with disabilities. The analysis focuses on the process of emotional transformation of the main character’s parents, their clash with their own expectations and prejudices, and the ways in which they overcome the fears associated with raising a child with Down syndrome. Through a literary interpretation, the article highlights the importance of education, empathy and social support in building an inclusive society. The issues raised are of particular relevance in the context of contemporary social policy, and Terakowska’s literary treatment of the topic provides a valuable space for reflection and dialogue.